Addressing Medical and Social Needs to Reduce Unnecessary Health Care Utilization and Costs: A Qualitative Study. Issue 3 (July 2022) - Liss, David T.; Guzman, Adriana; Walsh, Emily E.; Shaunfield, Sara; Brown, Tiffany
Abstract : This study explored the goals, and care delivery approaches, of 14 interventions to address patients' medical and social needs. In qualitative interviews with clinicians and researchers, several themes emerged. Participants frequently described their overall goal as meeting patients' diverse needs to prevent avoidable acute care utilization. Medical needs were addressed by ensuring patients received primary care and actively coordinating care across clinical settings. Participants perceived social needs as tightly linked with medical needs, as well as a need for interpersonal skills among intervention staff. Descriptions of overall approaches to meeting patients' needs frequently aligned with principles of trauma-informed care and patient-centered care.